“¿Qué estoy buscando?”: las motivaciones, interacciones e identidad de los usuarios de Grindr en Lima, Perú - Plaza Vidalón, Sergio Antonio (2020)
Grindr is a geolocation dating app for non-heterosexual male users, in which a profile is created in order to establish social interactions among the users. Ever since its creation, the app has been primarily used to arrange casual sex encounters, as well as to enroll in relationships, meet new people and for networking (Dodge, 2014). The aim of this thesis is to describe the many interactions that take place among the Grindr users in Lima, Peru, as well as to describe the motivations and gratifications of the usage of the app, consequences upon social interactions, the users’ own developed language and culture, discrimination, objectivation and segregation, stereotypes, and toxic masculinities that condemn the femininity and exalt masculinity.